Kegiatan Tumpek Wariga Dalam Tradisi Hindu Di Desa Penatih Bali - Rifqi Setiyawan Pradnya; Suswandari Suswandari (Purwadita : Jurnal Agama dan Budaya, 2022)
Human civilization is formed in various ways, both from nature and from humans themselves. From these two elements a belief can be formed between human beings so that mass belief or religion is created. In Bali itself, the Tumpek Wariga activity is a form of community religious ritual with cultural and spiritual values as a religious person. Tumpek wariga itself is a tradition of Hindu religion offering to God Almighty for the natural wealth given. By expressing this gratitude, the Hindu community in Penatih Bali village conducts religious activities simultaneously by carrying out various kinds of activities with the same goal of increasing spiritual values as a religious community. By using ethnographic research methods as well as literature studies and interviews with the community in Penatih Bali village, where the results of this study aim to introduce one of the local wisdoms that exist in Indonesia, how this cultural activity is still preserved by the community